Managing Future Challenges for Safety Demographic Change, Digitalisation and Complexity in the 2030s - Laroche, Hervé; Bieder, Corinne; Villena-López, Jesús (SpringerBriefs in Safety Management, 2022)
This open access book addresses the future of work and industry by 2040-a core interest for many disciplines inspiring a strong momentum for employment and training within the industrial world. The future of industrial safety in terms of technological risk-management, although of obvious concern to international actors in various industries, has been quite sparsely addressed. This brief reflects the viewpoints of experts who come from different academic disciplines and various sectors such as oil and gas, energy, transportation, and the digital and even the military worlds, as expressed in debates and discussions during a two-day international seminar. The contributors address such questions as: What influence will ageing and lack of digital skills in the workforce of the occidental world have on safety culture? What are the likely impacts of big data, artificial intelligence and autonomous technologies on decision-making, and on the roles and responsibilities of individual actors and whole organizations? What role have human beings in a world of accelerating changes? What effects will societal concerns and the entrance of new players have on technological risk management and governance? Managing Future Challenges for Safety will interest and influence researchers considering the future effects of a number of currently developing technologies and their practitioner counterparts working in industry and regulation.